O ensino de música na educação infantil da cidade de Natal: concepções e práticas docentes - Gomes, Carolina Chaves (2011)
Music education now covers several areas, stands out for this work the reality of early childhood education, specifically the music specialist teacher in this universe. Thus, the main objective of this study is to analyze the concepts and teaching practices that characterize the performance of music teachers in early childhood education in private and municipal public schools in Natal, Brazil. To this end, we attempted to verify: which schools offer special music classes in early childhood education; content and strategies that characterize these classes; the concepts of music-teaching professionals working in this reality; the professional profile of teachers, bypassing training, expectations, planning and evaluating lessons; and general dimensions related to infrastructure, workload, integrating educational and other aspects related to the insertion of music classes at the kindergarten, school reality. Methodologically, it was assumed a qualitative approach complemented by the quantitative side of research. Thus, two stages were established for the study: first, a survey of 208 schools with the identification of 20 professionals and a questionnaire of open and closed questions, admitting analysis using statistical software; and the second, two case studies through classroom observations and interviews conducted by two music educators working in early childhood education in private and municipal public schools in Natal. In the first step, among several aspects, it was observed that there is demand for music education in early childhood education, and, in the practices, the presence, in accordance with the literature, of game, playing and movement activities and use a repertoire of children's culture and percussion instruments. Concerning the accomplishment of the practices, the following difficulties were identified: the views of parents, teachers and administrators about music education, the role of music teacher as well as lack of musical materials to the detriment of the materials of common usage. Still, they believe that overcoming these limitations can occur primarily through the teacher's attitudes, education and training and investment in infrastructure. In relation to the reasons for working specifically with children's education, they highlight specific aspects of this universe, as repertoire, space and interaction with children. With regard to case studies, it was noted that teachers' practices are contextualized with their formation history and the specificity of the contexts that insert their school and students, and the main elements of its practice are specific to the infant universe and diversify their practices according to the availability of infrastructure. These teachers have broad goals that ensure flexibility in the definition of content, activities and repertoire, highlighting a specifically musical and sound related approach and an extra sound one. They held register of their projects, and lesson plans and observations and believe that music as extra-curricular activity is undemocratic, emphasizing the importance of music in the regular schools, especially in early childhood education. Thus, it is clear that the diversity of ideas, practices, and profiles along with the search for record, research, and reflection on the performance and musical education reflects a dialogue between music education and early childhood education, at the time these teachers working at this level of education.